PENERAPAN TERAPI REALITAS DALAM KONSELING KELOMPOK UNTUK MENINGKATKAN PERILAKU BERTANGUNGJAWAB PADA ANGGOTA KELOMPOK - Fadhilla Yusri (Jurnal Al-Taujih : Bingkai Bimbingan dan Konseling Islami, 2018)
Group counseling in schools attracts many school students, especially when learning how they often brainstorm about interests and concerns. During this time the implementation of group counseling in schools is done with the stages of activities that have been formulated practically. At the stage of group counseling during this time there has been no application of various approaches in these activities. The knowledge that school counselors have about various approaches is not followed by their application in group counseling activities. This article will discuss about the application of one approach that is reality in group counseling activities.